2016
DOI: 10.1097/tld.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Second Grade Listening Comprehension Using Prekindergarten Measures

Abstract: The purpose of this study was to determine prekindergarten predictors of listening comprehension in second grade. Methods: Within a large, 5-year longitudinal study, children progressing from prekindergarten to second grade were administered a comprehensive set of prekindergarten measures of foundational language skills (vocabulary and grammar), higher-level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Furthermore, we acknowledge that there are a number of factors that impact on learning to read, for example, fluency and working memory which were not monitored in this study (Alonzo, Yeomans-Maldonado, Murphy, & Bevens, 2016;Lepola, Lynch, Kiuru, Laakkonen, & Niemi, 2016). There is also considerable research into learning environments, behaviour, and attendance which significantly impact academic skills, however these were not included in the current study (Buckingham et al, 2013;Hay & Fielding-Barnsley, 2009;Justice, Mashburn, Pence, & Wiggins, 2008;Tucker-Drob, 2012).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Furthermore, we acknowledge that there are a number of factors that impact on learning to read, for example, fluency and working memory which were not monitored in this study (Alonzo, Yeomans-Maldonado, Murphy, & Bevens, 2016;Lepola, Lynch, Kiuru, Laakkonen, & Niemi, 2016). There is also considerable research into learning environments, behaviour, and attendance which significantly impact academic skills, however these were not included in the current study (Buckingham et al, 2013;Hay & Fielding-Barnsley, 2009;Justice, Mashburn, Pence, & Wiggins, 2008;Tucker-Drob, 2012).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Alonzo, Yeomans‐Maldonado, Murphy, Bevens, and LARRC (2016) examined prekindergarten language‐related predictors of grade 2 listening comprehension. They found that a variety of language‐related predictors (including listening comprehension, vocabulary, word structure knowledge, and grammar) accounted for substantial variance (55%) in grade 2 listening comprehension.…”
Section: The Structure Of Language and Its Relation To Reading Comprementioning
confidence: 99%
“…Oral language skills such as vocabulary are also crucial for comprehending decoded text (Elleman, Lindo, Morphy, & Compton, 2009;National Institute of Child Health and Human Development, 2000). Furthermore, although not included in the National Reading Panel Report due to lack of evidence at the time, recent studies have revealed that oral language skills beyond vocabulary such as grammatical knowledge and listening comprehension as well as higher order cognitive skills (e.g., inference, perspective taking) are necessary for reading comprehension (e.g., Alonzo, Yeomans-Maldonado, Murphy, & Bevens, 2016;Florit, Roch, Alto e, & Levorato, 2009;Florit, Roch, & Levorato, 2014;Kendeou, Bohn-Gettler, White, & van den Broek, 2008;Kim, 2017).…”
mentioning
confidence: 99%